The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1590/0104-6632.20140312s00001956
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection of nanofluids over a convectively heated vertical plate embedded in a porous medium

Abstract: -In this paper, the natural convective flow of nanofluids over a convectively heated vertical plate in a saturated Darcy porous medium is studied numerically. The governing equations are transformed into a set of ordinary differential equations by using appropriate similarity variables, and they are numerically solved using the fourth-order Runge-Kutta method associated with the Gauss-Newton method. The effects of parametric variation of the Brownian motion parameter (Nb), thermophoresis parameter (Nt) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 91%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 91%
“…Direct simulation analysis based on CFD techniques was performed using the ANSYS Fluent 14.0 software, where the set of governing equations is discretized through a multigrid finite volume approach. The ANSYS-CFD package is widely used to solve natural convection problems with high accuracy (see Fontana et al (2011Fontana et al ( , 2013a and Ghalambaz et al (2014), for example). The hypothesis applied, the governing equations and the boundary conditions applied at the solid walls used in the CFD simulation are the same as those previously described for the LSA.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…The deposition characteristics of nanosized particle in convectional straight tube, a 90°90° square bend tube, the sodium caboxymethyl cellulose, including the titania nanoparticles in unsteady flow of based nanofluid, the angular momentum and microinertia characteristics on solid sphere, over vertical plate have been investigated by Ramirez‐Tijerina et al, 8 Hussanan and Nguyen, 9 Swalmeh et al, 10 Yin et al, 11 and Abid et al 12 Furthermore, the effects of Biot number with thermal convection on non‐Newtonian fluid over an isothermal sphere, the effects of mixed convection on micropolar nanofluid containing oxide nanoparticles, and natural convection of nanofluid in a porous medium past heated vertical plate have been examined by Pop, 13 Gaffar et al, 14 Hamzeh et al, 15 and Ghalambaz et al 16 The results demonstrate that enlarge values of mixed convection constraint and nanoparticle volume fraction enhance thermal convection and reduce local skin friction in methanol and kerosene oil‐based nanofluid. As the thermal volumetric expansion boost due to the buoyancy force, which fall the density of fluid acts the skin friction coefficients reduce.…”
Section: Introductionmentioning
confidence: 99%